Learning Agility: The Nexus Between Learning Organization, Transformative Learning, and Adaptive Performance - Doo H. Lim; Min Hee Yoo; Junghwan Kim; Spencer A. Brickell (Adult Education Research Conference, 2017)
The purpose of this study is to establish a model of learning agility that is connected with transformative learning and the double-loop learning of organizational learning. Also, this study aims to identify the mediating role of learning agility on the relationship between learning organization, transformative learning, and adaptive performance.
Keywords: learning agility; learning organization; transformative learning; adaptive performance